Advances in Stimuli‐Responsive Polypeptide Nanogels. Issue 3 (25th January 2018) - Jiang, Zhongyu; Chen, Jinjin; Cui, Liguo; Zhuang, Xiuli; Ding, Jianxun; Chen, Xuesi
Abstract: Polymer nanogels, which are nanosized particles of hydrogels formed by physically or chemically crosslinking polymers, are one of the most promising nanoplatforms for use in biomedical applications, including drug delivery, gene therapy, and bioimaging. Polypeptide nanogels exhibit many advantages for applications in biomedical fields, including stable 3D structures, high drug‐loading efficiency, excellent biocompatibility, stimuli responsiveness, and so forth. More specifically, smart polypeptide nanogels undergo suitable transitions under endogenous (e.g., reduction, reactive oxygen species, pH, and enzymes) or exogenous stimuli (e.g., light, temperature, voltage, and magnetic fields) for on‐demand drug delivery. Here, a comprehensive introduction to the preparation and applications of diverse stimuli‐responsive polypeptide nanogels is given. Moreover, the opportunities and challenges of polypeptide nanogels for the development of biomedicine are briefly predicted. Abstract : Recent advances in mono and multiresponsive polypeptide nanogels prepared by crosslinking postpolymerization or ring‐opening polymerization of functional monomers are highlighted. These smart polypeptide nanogels undergo suitable transitions, e.g., swelling, shrinking, or disintegration under endogenous or exogenous stimuli for on‐demand drug delivery. Moreover, the opportunities and challenges of polypeptide nanogels for the development of biomedicines are briefly predicted.